Targeting NCK-Mediated Endothelial Cell Front-Rear Polarity Inhibits Neovascularization. Issue 4 (26th January 2016) - Dubrac, Alexandre; Genet, Gael; Ola, Roxana; Zhang, Feng; Pibouin-Fragner, Laurence; Han, Jinah; Zhang, Jiasheng; Thomas, Jean-Léon; Chedotal, Alain; Schwartz, Martin A.; Eichmann, Anne
Abstract : Background—: Sprouting angiogenesis is a key process driving blood vessel growth in ischemic tissues and an important drug target in a number of diseases, including wet macular degeneration and wound healing. Endothelial cells forming the sprout must develop front-rear polarity to allow sprout extension. The adaptor proteins Nck1 and 2 are known regulators of cytoskeletal dynamics and polarity, but their function in angiogenesis is poorly understood. Here, we show that the Nck adaptors are required for endothelial cell front-rear polarity and migration downstream of the angiogenic growth factors VEGF-A and Slit2. Methods and Results—: Mice carrying inducible, endothelial-specific Nck1/2 deletions fail to develop front-rear polarized vessel sprouts and exhibit severe angiogenesis defects in the postnatal retina and during embryonic development. Inactivation of NCK1 and 2 inhibits polarity by preventing Cdc42 and Pak2 activation by VEGF-A and Slit2. Mechanistically, NCK binding to ROBO1 is required for both Slit2- and VEGF-induced front-rear polarity. Selective inhibition of polarized endothelial cell migration by targeting Nck1/2 prevents hypersprouting induced by Notch or Bmp signaling inhibition, and pathological ocular neovascularization and wound healing, as well. Conclusions—: These data reveal a novel signal integration mechanism involving NCK1/2, ROBO1/2, and VEGFR2 that controls endothelial cell front-rear polarity during sprouting angiogenesis. Abstract : Supplemental Digital Content is available in the text.